Os Jogos digitais para os alunos com TEA: a tecnologia assistiva como ferramenta de intervenção no AEE no centro Moendy Akã, Bragança-PA - VINAGRE, Swany Furtado (2021)
This study aims to analyze the use of digital games as an intervention tool in Specialized Educational Care with students with Autistic Spectrum Disorder. Having as applicable objectives: identify the benefits of digital games as a pedagogical resource in Specialized Educational Care (ESA), create and apply digital games as innovative methods of interaction in teaching and learning, understand how students interact when using digital games in the process of teaching and learning, from the qualitative methodological approach of bibliographic survey, documentary research. The construction of the games took place through participant observation in the ESA at the Reference Center for Specialized Educational Therapy (CRATEE) - Moendy Akã in the municipality of Bragança-PA and interviews with ESA teachers working at the Center. From the data collection, start building three games: car racing core game, vowel game and syllable family game, use or editor of the Power Point presentation, playback display using music, images and subjects of preference of the students and the contents to be worked. As the applications of the games occur from April to June 2019, with four children with ASD who perform or receive care at CRATEE-Moendy. The results show us that children with ASD interacted significantly with games, especially with those who had their development developed as image and music of their choice.